2002
DOI: 10.1111/j.1432-2277.2002.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of testosterone and estrogens on chronic allograft nephropathy

Abstract: In the present study we investigated whether donor gender or the effects of sex hormones play the greater role in the development of chronic allograft nephropathy. Kidneys of male and female Fisher rats were orthotopically transplanted into castrated male Lewis recipients. Animals were treated with testosterone, estradiol, or vehicle and the kidneys were harvested 20 weeks after transplantation for histological, immunohistological, and molecular analysis. Testosterone treatment resulted in increased proteinuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Muller et al (34) demonstrated that kidneys transplanted into ovariectomized, testosterone-treated females demonstrated increased interstitial fibrosis, glomerular sclerosis, proteinuria, and increased expression of fibronectin and TGF-␤1 compared with estradiol treated ovariectomized females. Similarly, Antus et al (2) found that kidneys transplanted into castrate male rats treated with testosterone exhibited increased proteinuria, profound glomerulosclerosis, and increased TGF-␤1 and platelet-derived growth factor-A and -B expression, irrespective of donor gender, compared with estradiol or vehicle-treated castrated male rats. The authors further demonstrated that the adverse effects of androgens on chronic allograft nephropathy are mediated by dihydrotestosterone, as the histologic deterioration and expression of profibrotic mediators were inhibited by treatment with both the anti-androgen flutamide and the 5 alpha-reductase inhibitor finasteride (1).…”
Section: Discussionmentioning
confidence: 99%
“…Muller et al (34) demonstrated that kidneys transplanted into ovariectomized, testosterone-treated females demonstrated increased interstitial fibrosis, glomerular sclerosis, proteinuria, and increased expression of fibronectin and TGF-␤1 compared with estradiol treated ovariectomized females. Similarly, Antus et al (2) found that kidneys transplanted into castrate male rats treated with testosterone exhibited increased proteinuria, profound glomerulosclerosis, and increased TGF-␤1 and platelet-derived growth factor-A and -B expression, irrespective of donor gender, compared with estradiol or vehicle-treated castrated male rats. The authors further demonstrated that the adverse effects of androgens on chronic allograft nephropathy are mediated by dihydrotestosterone, as the histologic deterioration and expression of profibrotic mediators were inhibited by treatment with both the anti-androgen flutamide and the 5 alpha-reductase inhibitor finasteride (1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, renoprotection by estrogen is described in other forms of renal injury, including rat models of chronic allograft nephropathy (CAN) (15,24,25), age-related glomerular damage (29), and hypertensive nephrosclerosis (30). The role of estrogen receptors in this process remains a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have focused on the effects of estrogen and testosterone on the intrinsic tissue tolerance of ischemia through differential expression of oxidative scavengers, HSPs, or other mediators (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Moreover, a number of reports describe sex differences in the development of chronic injury patterns in animal transplant models (15,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens or estrogen metabolites ameliorate renal damage in some (5) but not all (6,7) models of renal damage. The beneficial effect of estrogen was also noted in allograft nephropathy (8). Potential explanations for the discrepancies are that different pathomechanisms operate in the various animal models or that differences in the administered doses, application modalities, and types of estrogen metabolites account for the differences (9 -11).…”
mentioning
confidence: 99%